The Relationship of Mother's Knowledge, Corner Care, and Education With the Time of Numbers Droping in Newbirth Babies at Surya Adi Poskesdes in 2021 - Ira Maya Sopa Ginting; Satra Yunola; Turiyani Turiyani (Science Midwifery, 2022)
Infant mortality has a close relationship with the quality of delivery services, less than optimal handling of newborns (BBL) The main causes of newborn mortality in 2018 are asphyxia as much as 23%, infection as much as 36%, and premature as much as 28%. To determine the relationship between knowledge, umbilical cord care, and length of umbilical cord detachment in newborns. This study used an analytical survey method using a cross sectional approach. The population is 32 mothers who have babies aged 0 to 6 months at Poskesdes Surya Adi Village, Mesuji District, OKI Regency. Samples were taken using a total sampling technique of 32 samples, using univariate and bivariate analysis. The results of the univariate analysis of 32 respondents who had babies aged 0 to 6 months who experienced fast umbilical cord detachment 20 respondents (63%) experienced normal umbilical cord detachment 11 respondents (34%) and length of umbilical cord detachment 1 respondent (3 %). The results of bivariate analysis showed that there was a relationship between mother's knowledge and the length of umbilical cord detachment in newborns (p=0.000), there was no relationship between umbilical cord care methods and the length of umbilical cord detachment in newborns (p = 0.008), there was no relationship between history of counseling (IEC) with length of umbilical cord detachment in newborns (p = 0.007). There is a relationship between mother.